The Genealogy of the Land Mafia: A Historical Analysis in the National Land System - Fitriah Alfiany, Temmy; Pramudita, Roni Renaldi; Mulyanti, Asti Sri; Suyaman, Prahasti (Journal of Law, Politic and Humanities, 2025)
The need for land in Indonesia cannot be separated from its people. This can be seen from how it benefits national development and is a source of livelihood that is integrated. However, the development of national development that is increasingly incessant makes the availability of land even thinner. Therefore, from this was born the land case, which today has transformed into a land mafia that has a motive to take over the land with various tactics and actions. The method used in this study uses normative juridical methods and primary data sources from the study of the community. The purpose of this study is to provide a historical analysis of the birth of the land mafia in the national land system. The findings show that the land mafia in Indonesia was born due to the loss of land owned by the people taken by the colonialists. In this context, the land mafia took advantage of the already unstable situation to take over the rights to land that should have been owned by the people, and arrived at the same polarization until now